Anterior surface opacification of intraocular lenses after Descemet's stripping automated endothelial keratoplasty. (16th December 2015) - Ní Mhéalóid, Áine; Fulcher, Tim; O'Keefe, Michael
Abstract : Descemet's stripping automated endothelial keratoplasty (DSAEK) is today recognised as the surgical procedure of choice for corneal endothelial dysfunction. 1 The triple procedure (either staged or combined), whereby cataract surgery can be performed at the same time as endothelial keratoplasty, is well suited for patients with Fuch's endothelial dystrophy with decreased vision due to endothelial guttata, early stromal oedema and cataract formation. 2 Recognised complications of DSAEK include donor graft detachment/dislocation, primary graft failure and pupillary block by air. 2–4 Intraocular lens (IOL) opacification is a complication that is becoming apparent in patients who have undergone DSAEK and, to date, no definitive mechanism of such opacification has been discovered. Primary postoperative optic opacification of hydrophilic acrylic IOL designs has been attributed to the formation of calcium phosphate deposits. 5 6 This has led to changes in lens designs, manufacturing processes and packaging. 7 Secondary calcification is thought to be caused by environmental factors unrelated to the IOL model, such as breakdown of the blood–aqueous barrier. 8 In this report, four cases of IOL anterior surface opacification are described in patients who required both cataract surgery and DSAEK. Only one case had cataract surgery and DSAEK performed concurrently, with the remainder having DSAEK performed at variable timeframes after cataract surgery.